Abrogation of IFN-γ Signaling May not Worsen Sensitivity to PD-1/PD-L1 Blockade - Vackova, Julie; Piatakova, Adrianna; Polakova, Ingrid; Smahel, Michal (International journal of molecular sciences, 2020)
Programmed cell death protein 1 (PD-1)/PD-1 ligand 1 (PD-L1) blockade is a promising therapy for various cancer types, but most patients are still resistant. Therefore, a larger number of predictive biomarkers is necessary. In this study, we assessed whether a loss-of-function mutation of the interferon (IFN)-γ receptor 1 (IFNGR1) in tumor cells can interfere with anti-PD-L1 therapy. For this purpose, we used the mouse oncogenic TC-1 cell line expressing PD-L1 and major histocompatibility complex class I (MHC-I) molecules and its TC-1/A9 clone with reversibly downregulated PD-L1 and MHC-I expression. Using the CRISPR/Cas9 system, we generated cells with deactivated IFNGR1 (TC-1/dIfngr1 and TC-1/A9/dIfngr1). In tumors, IFNGR1 deactivation did not lead to PD-L1 or MHC-I reduction on tumor cells. From potential inducers, mainly IFN-α and IFN-β enhanced PD-L1 and MHC-I expression on TC-1/dIfngr1 and TC-1/A9/dIfngr1 cells in vitro. Neutralization of the IFN-α/IFN-β receptor confirmed the effect of these cytokines in vivo. Combined immunotherapy with PD-L1 blockade and DNA vaccination showed that IFNGR1 deactivation did not reduce tumor sensitivity to anti-PD-L1. Thus, the impairment of IFN-γ signaling may not be sufficient for PD-L1 and MHC-I reduction on tumor cells and resistance to PD-L1 blockade, and thus should not be used as a single predictive marker for anti-PD-1/PD-L1 cancer therapy.
Keywords: interferon gama; B7-H1 Antigen; cancer; Interferon-gamma; immune checkpoint therapy; MHC class I; transformované buněčné linie; antigeny CD274; Cell Line, Transformed; experimentální nádory; antigeny CD279; myši inbrední C57BL; Mice; Tumor Cells, Cultured; Programmed Cell Death 1 Receptor; IFN-α; ženské pohlaví; imunoterapie; zvířata; IFN-β; IFNGR1; Neoplasms, Experimental; PD-1/PD-L1; myši; Immunotherapy; protinádorové látky imunologicky aktivní; Female; nádorové buňky kultivované; Antineoplastic Agents, Immunological; Mice, Inbred C57BL; Animals